MRI tracking of polyethylene glycol-coated superparamagnetic iron oxide-labelled placenta-derived mesenchymal stem cells toward glioblastoma stem-like cells in a mouse model. (12th November 2018) - Hsu, Fei-Ting; Wei, Zung-Hang; Hsuan, Yogi Chang-Yo; Lin, Willie; Su, Yu-Chin; Liao, Chia-Hui; Hsieh, Chia-Ling
Abstract: Mesenchymal stem cells (MSCs) that display homing and infiltration properties towards tumor cells are a promising cellular targeting vector for brain tumor therapy but are limited to local-regional delivery in current preclinical models. Here, we investigated whether placenta-derived MSCs (P-MSCs) are a superior cellular vector for systemic targeting of glioblastoma stem-like cells (GSCs), with an imaging modality to real-time monitor the trafficking P-MSCs to glioblastoma sites. Results demonstrated that P-MSCs had greater migratory activity towards GSCs and across blood–brain barrier compared with bone marrow-derived MSCs, and this activity was enhanced by hypoxia precondition. Chemokine ligand 5 was identified as a chemoattractant responsible for the glioblastoma tropism of P-MSCs. Polyethylene glycol-coated superparamagnetic iron oxide (PEG–SPIO) was synthesized for cellular labelling and imaging P-MSCs, displaying high cellular uptake and no cytotoxic effect on P-MSCs cell proliferation or stemness property. The homing effects of intravenously administered PEG–SPIO-labelled P-MSCs towards intracerebral GSCs were able to be detected in mice models through T2-weighted magnetic resonance imaging (MRI). This study suggests the possibility of innovative systemic P-MSC-based cell therapy for aggressive GSCs, developing a state-of-the-art theranostic technique for real-time tracking of therapeutic P-MSCs tumor infiltration through cellular MRI.